Thematic Learning Book with Local Wisdom Insight of Boyolali Municipality for Primary School Students - Kartikasari, Farida Nur; Kustiono, Kustiono; Utomo, Udi (Universitas Negeri Semarang, 2020)
2013 curriculum regulates learning to be adjusted to surrounding living environment of students. Therefore, thematic Textbook with local wisdom insight should be developed by providing contextual examples. This research aims to develop thematic Textbook with local wisdom insight oriented to science literacy and environmental care characteristics. This mixed method research used explanatory design. The quantitative data was analyzed by pre-experiment typed one shot case study. The qualitative data was analyzed by flow analysis, consisting of reduction, presentation, and conclusion of the data. The data collection was done by interview, questionnaire, and test. The findings were, an interesting thematic Textbook with local wisdom insight to be learned by students since it provides contextual and detailed examples based on the materials and learning by using thematic Textbook with local wisdom insight could improve learning outcome as proven by t test. It showed tcount > ttable 5.661 > 1.67469. Thus a thematic teaching book with insightful local wisdom can be interesting to use in learning. The learning book have valuable benefit to introduces, students to the natural potential in its environment.